Termination of a simulated failed corn stand and timing interval for replanting corn or soybean - Gregory A. Mangialardi; Jason A. Bond; Drew M. Gholson; Tom W. Allen; Justin M. McCoy; Hunter D. Bowman; Franklin R. Kelly (Weed Technology)
Termination of an existing failed corn stand before replanting is essential. Two studies were conducted in Stoneville and Verona, MS, from 2020 to 2021 to evaluate timing of corn or soybean replanting following different herbicide treatments applied to simulated failed stands of corn. Treatments included paraquat alone at 841 g ai ha−1, paraquat at 841 g ha−1 + metribuzin at 211 g ai ha−1, and clethodim at 51 g ai ha−1 + glyphosate at 1,121 g ae ha−1 applied at the V2 growth stage. Replant timings were 1 and 7 d after herbicide treatment (DAT). Pooled across replant timings, paraquat + metribuzin provided the greatest control 3 DAT compared with other treatments in both studies. At 14 and 21 DAT, clethodim + glyphosate controlled more corn than did paraquat + metribuzin and paraquat alone. Control of a simulated failed corn stand with paraquat alone never exceeded 50% at 3 to 21 DAT. Soybean yield in all plots receiving herbicide treatment targeting simulated failed corn stands were similar and ≥2,150 kg ha−1. When applied at the V2 corn growth stage, both clethodim + glyphosate and paraquat + metribuzin controlled a simulated failed stand of corn. This study demonstrated the importance of terminating failed stands of corn before replanting because of dramatic reductions in yield in the plots not treated with herbicide.